Genre, mouvements populaires urbains et environnement - Verschuur, Christine (Graduate Institute Publications, 2007)
Le désordre urbain et les défis environnementaux que nous connaissons ne sont pas perçus ni vécus pareillement aux Suds et aux Nords, par les femmes et les hommes, par les puissants et les exclus. Les mouvements populaires urbains et de lutte pour l'environnement participent de la réflexion sur les changements de paradigme de développement qui sont urgents et nécessaires. La perspective de genre donne des clés de lecture pour comprendre comment les asymétries féminin-masculin structurent la perception et l’organisation concrète de la vie sociale. La forte présence des femmes dans les organisations urbaines et de lutte pour l’environnement est généralement peu ou pas reconnue. Ce livre explore certains mouvements populaires urbains, qui participent au travail de prise de conscience et de revendications de droits et qui permettent ainsi d'envisager des alternatives sur des territoires de vie, sans plus attendre.
Keywords: 2000 à aujourd'hui; approches et analyses; changements climatiques; environnement; féminisme décolonial; histoire et politique; intersectionnalité; justice climatique; justice sociale; outils; ouvrages de références; projet charge mentale; périodes historiques; thématiques; écoféminisme

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme